A DXA Primer for the Practicing Clinician A Case-Based Manual for Understanding and Interpreting Bone Densitometry - Licata, Angelo A.; Williams, Susan E.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Dual-energy X-ray absorptiometry (DXA) is the principal x-ray technology used to diagnose osteoporosis in its early, asymptomatic stages, to assess treatment efficacy, and to guide treatment decisions. It remains the gold standard today. A DXA Primer for the Practicing Clinician: A Case-Based Manual for Understanding and Interpreting Bone Densitometry is based on actual clinical encounters and treatment dilemmas encountered by the authors. The content is derived from years of clinical practice and presentations given by the authors at regional and national conferences. It exemplifies not only the complete body of knowledge provided through these lectures but also the full range of previously undiscussed nuances of DXA interpretation. This practical, easy-to-read text captures many of the common challenges of DXA interpretation that clinicians often encounter. The central focus of the book is the presentation of what is normal and what is problematic when using DXA. It presents real-life case histories, their corresponding DXA images, the problems encountered and their solutions. Unique in approach and presentation, this one-of-a-kind case-based manual will be of immense value to all clinicians—and students—motivated to optimize their diagnostic skills and assessment of patients with abnormal bone densities.
Keywords: Endocrinology .; Rheumatology; Endocrinology; Rheumatology